THE ROLE OF INTERNET OF THINGS (IoT) IN SUPPORTING DIGITAL TRANSFORMATION - Sara Abdelli; Farid Ben Abid (International Journal of Innovative Technologies in Social Science, 2025)
This study investigates the pivotal role of the Internet of Things (IoT) in driving and accelerating digital transformation across multiple sectors. Employing a qualitative analytical methodology, the research draws upon an extensive review of recent scholarly literature and real-world industry case studies. The analysis delves into the fundamental components of IoT systems, their architectural design, and their practical applications in areas such as healthcare, manufacturing, transportation, agriculture, and smart urban environments. Additionally, the study identifies key barriers to widespread IoT adoption, including cybersecurity threats, interoperability challenges, and regulatory ambiguities. The findings underscore IoT’s substantial impact on enhancing operational performance and decision-making through real-time data processing and automated processes. While notable obstacles remain, the research concludes that the strategic deployment of IoT technologies yields significant advantages-ranging from cost savings and process optimization to increased organizational competitiveness. To unlock the full transformative capacity of IoT, the study highlights the necessity of implementing robust cybersecurity frameworks, coherent regulatory policies, and standardized integration protocols.